Given that a and b are positive integers, where a > b , such that
5 + 2 6 = a + b ,
find the value of a − b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
square LHS & RHS then we get 5 + 2√6 = a+b+2√ab ( (a+b)^2 = a^2 + b^2 + 2ab). On comparing both the sides we see that a+b = 5 and ab = 6. hence we conclude that a , b = 3 , 2 respectively because a>b. therefore a-b = 3-2 = 1
Squaring both sides,we get: 5 + 2 6 = a + b + 2 a b → a + b = 5 → 2 a b = 2 6 → a b = 6 We see that a = 3 , b = 2 is a solution so a + b = 3 + 2 → a − b = 3 − 2 = 1
i used same solution, direct square and substitution gives a+b=5 and a x b =6
We are given the equation
5 + 2 6 = a + b
Where a > b
First we square both sides to get
5 + 2 6 = a 2 + 2 a b + b 2
5 + 2 6 = a + b + 2 a b
From this we can gather that
a + b = 5
a b = 6
We can use these equation to find a and b
b = 5 − a
a ( 5 − a ) = 6
5 a − a 2 = 6
− a 2 + 5 a − 6 = 0
a 2 − 5 a + 6 = 0
Now we can use the quadratic formula for a
a = 2 ( 1 ) − ( − 5 ) ± ( − 5 ) 2 − 4 ( 1 ) ( 6 )
a = 2 5 ± 1
a = 3 , 2
Alternately you can also factorise.
We know a > b and that a + b = 5 so a can't be equal to 2 as that would suggest that b = 3 which is incorrect. This means that a = 3 and b = 2 so
a − b = 3 − 2 = 1
sqrt(5+(2sqrt(6)))=sqrt(5+6)=sqrt(5)+sqrt(6) but a > b so sqrt(5+6)=sqrt(6)+sqrt(5) so the answer is 6-5=1
5+2Sqrt(6)=a+b+2Sqrt(ab)
So a+b=5 ab=6
a=3 b=2 --> a-b=1
Problem Loading...
Note Loading...
Set Loading...
Note that 5 + 2 6 = 3 2 + 2 3 2 + 2 2 = ( 3 + 2 ) 2 . Since 3 + 2 > 0 , we have 5 + 2 6 = ( 3 + 2 ) 2 = 3 + 2 . Hence, a = 3 , b = 2 and a − b = 1 .